The effect of Vitamin E treatment on the development of myringosclerosis after ventilation tube insertion - (:unkn) unknown (ELSEVIER IRELAND LTD, 2006)
Objectives: Recent studies have established the relationship between the reactive oxygen species and myringosclerosis. Furthermore several antioxidants have been known to prevent myringosclerosis. All the previous studies supporting this hypothesis have been performed on animals. The aim of our study is to investigate the possible effect of Vitamin E on the development of tympanosclerosis after VT insertion on human subjects. Methods: 72 children undergoing myringotomy and VT insertion were included in the study. Vitamin E was applied to the right ear and no treatment was appplied to the left ear. Both ears were examined at the end of 9 months with otomicroscopy. Myringosclerosis formation at the end of the study period was noted for each ear. Results: Myringosclerosis was found in 33 of the 144 ears. The overall incidence was 22.9%. While 22 (30.6%) of the 72 left ears showed myringosclerosis otomicroscopically, in only 11 (15.3%) of the 72 right ears that were treated with Vitamin E was myringosclerosis observed at the end of the study period. Of these nine cases were bilateral. Conclusion: Animal studies have well, documented the development of myringosclerosis after myringotomy and VT insertion and beneficial effects of different antioxidants. Our study has shown similar results in human subjects. Further clinical studies consisting of a larger patient population are needed to bring about routine clinical use of antioxidants in myringotomy and VT insertion. (C) 2005 Elsevier Ireland Ltd. All. rights reserved.
Keywords: myringosclerosis; ventilation tube insertion; Vitamin E; TYMPANIC MEMBRANES; TYMPANOSCLEROSIS; MYRINGOTOMY; OTITIS